PENGARUH KOMPETENSI PEDAGOGIK GURU BAHASA INGGRIS TERHADAP INDEPENDENSI BELAJAR SISWA - Wasino (LPPM Universitas Asa Indonesia, 2018)
This study aims to determine the effect of teacher pedagogical competence and student learning independence on speaking/communicating skills in English students at SMKN 37and SMKN 57students in South Jakarta. This study is to examine the effect of teacher pedagogical competence and student learning independence on English speaking / communicating skills, the authors use validity test using data correlation coefficient analysis with Normaly Test, Leneary Test, Multicollinearity Test, Heterokedasiticity Test and Normal Residual Test. Data analysis was carried out through simple correlation techniques, partial correlation techniques and multiple correlation, the results of the regression analysis. Data analysis was carried out through simple correlation techniques, partial correlation techniques and multiple correlation, the results of the regression analysis were, Y = 56,723 + 0,115X1 + 0,130 X2. Students' perceptions on teacher pedagogical competence give 0.043 or 43,%. The contribution of the independent variables consisting of the Perception of the Teacher's Pedagogic Competence and Learning Independence on the English Speaking Ability of the State Vocational Middle School Students in South Jakarta is partially contributed 0.295 or 29.5% While the remaining 64.1% is influenced or explained by other variables not included in the research model.